2018
DOI: 10.1186/s41065-018-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of grain number per spike by RNA interference of cytokinin oxidase 2 gene in bread wheat

Abstract: BackgroundThis study aimed to validate the function of CKX gene on grain numbers in wheat.Methodswe constructed and transformed a RNA interference expression vector of TaCKX2.4 in bread wheat line NB1. Southern blotting analysis was used to select transgenic plants with single copy. The expression of TaCKX2.4 gene was estimated by Quantitative real-time PCR (qRT-PCR) analysis. Finally, the relation between expression of TaCKX2.4 gene and grain numbers was validated.ResultsTotally, 20 positive independent event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
2
23
1
Order By: Relevance
“…The same effect of elevated grain number, spike number, and yield was reported for RNAi-silenced HvCKX1 in barley [20,21,24] and repeated for the same gene under field conditions [25]. Moreover, significantly increased grain number per spike was found as the effect of the TaCKX2.4 gene silencing by RNAi [26]. Knock-out mutation of HvCKX1 by CRISPR/Cas9 editing had a limited effect on yield productivity, however significantly decreased CKX enzyme activity in young spikes and 10-day old roots corresponded to greater root length, numbers of root hairs and increased surface area [27].…”
Section: Introductionsupporting
confidence: 69%
“…The same effect of elevated grain number, spike number, and yield was reported for RNAi-silenced HvCKX1 in barley [20,21,24] and repeated for the same gene under field conditions [25]. Moreover, significantly increased grain number per spike was found as the effect of the TaCKX2.4 gene silencing by RNAi [26]. Knock-out mutation of HvCKX1 by CRISPR/Cas9 editing had a limited effect on yield productivity, however significantly decreased CKX enzyme activity in young spikes and 10-day old roots corresponded to greater root length, numbers of root hairs and increased surface area [27].…”
Section: Introductionsupporting
confidence: 69%
“…The effect of CKX on important agricultural traits has been known at least since the iconic identification of OsCKX 2 as the determinant of grain yields in rice [ 225 ]. Similar results were observed in other works [ 226 , 227 , 228 , 229 ] for which lower CKX expression led to more tillering, an increased number of siliques and/or seeds, and thus to higher yield. Interestingly, Zhang et al [ 230 ] observed a positive correlation between the grain number per spike and the expression of two TaCKX 2 genes in young spikes.…”
Section: Deactivation Of Cytokininssupporting
confidence: 91%
“…The overexpression of CKX genes leads to cytokinin-deficiency phenotype, such as an enlarged root system, reduced activity of the vegetative and floral shoot apical meristem, and an earlier differentiation of plastids and reduction of chlorophyll content in leaves [ 15 , 19 ]. On the other hand, CKX-deficient mutants showed an increased number of reproductive organs and higher seed yield in Arabidopsis, rice, barley or wheat [ 5 , 6 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%